DIAGNOSIS OF SICKLE CELL ANEMIA BY Dde 1 ENZYME BASED RFLP - ARUNIMA KARKUN; SANJANA BHAGAT (The Bioscan, 2011)
Sickle cell anemia is an autosomal recessive genetic disease, resulted by the substitution of valine for glutamic acid at position 6 of the beta globin gene leads to configurational change in hemoglobin of RBC and finally alteration in shape (sickle cell) and loss of retention capacity of oxygen. Its inheritance is based on Mendelian pattern and abundantly found across the world. Its diagnostic confirmation is always a confusing problem for the health worker. In the present study a molecular method for the confirmed diagnosis has been worked out by RFLP method using Dde1 enzyme. After DNA isolation, PCR amplification and RFLP application by Dde1 enzyme, one new bands of treated DNA with 376 bp and diagnostic band for sickling besides normal bands of 201bp and 175bp was found. The new bands of 376bp by using Dde1 enzyme confirm sickle cell anemia.